The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/pec.0000000000002786
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Interrater Reliability of Point-of-Care Ultrasonography Image Interpretation for Intussusception

Abstract: The aim of this study was to determine the accuracy and interrater reliability of (1) point-of-care ultrasound (POCUS) image interpretation for identification of intussusception and (2) reliability of secondary signs associated with intussusception among experts compared with novice POCUS reviewers. Methods:We conducted a planned secondary analysis of a prospective, convenience sample of children aged 3 months to 6 years who were evaluated with POCUS for intussusception across 17 international pediatric emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…Bergmann et al also revealed a similarly high rate of agreement of diagnostic accuracy using POCUS vs. RADUS (97%) and evaluated POCUS users’ ability to identify primary intussusception as well as secondary sonographic findings such as the presence of free fluid (83.3%), decreased color Doppler signal (95.7%) and presence of echogenic foci (80%). POCUS also expedited time to diagnosis, with median POCUS scan time of 6 min and RADUS scan time of 65 min [20].…”
Section: Pediatric Updatementioning
confidence: 99%
“…Bergmann et al also revealed a similarly high rate of agreement of diagnostic accuracy using POCUS vs. RADUS (97%) and evaluated POCUS users’ ability to identify primary intussusception as well as secondary sonographic findings such as the presence of free fluid (83.3%), decreased color Doppler signal (95.7%) and presence of echogenic foci (80%). POCUS also expedited time to diagnosis, with median POCUS scan time of 6 min and RADUS scan time of 65 min [20].…”
Section: Pediatric Updatementioning
confidence: 99%